COMMUNITY PSYCHOLOGY AND CIVIL SOCIETY: OPPORTUNITIES FOR GROWTH IN EGYPT AND LEBANON. Issue 1 (January 2015) - Amer, Mona M.; El‐Sayeh, Salma; Fayad, Yasmine; Khoury, Brigitte
<x xml:space="preserve">Abstract</x> Western theories and products, focused mostly on the individual level of analysis, inform psychology in Egypt and Lebanon. Psychologists in these nations have not yet played a significant role in addressing systemic community priorities, such as poverty and politically motivated violence. In the absence of community psychology, a vibrant network of civil society organizations has emerged to address urgent national concerns. We discuss and critique three types of civil society efforts that intersect with community psychology values and practice: community development, refugee services, and human rights advocacy. The emerging specialization of community psychology can address limitations of these fields and provide an alternative psychological perspective to community practice. This article examines how Egyptian and Lebanese community psychologies may transpire, including the roles community psychologists can play, values that may be integrated in this work, and considerations for formalizing training programs.